(untitled) (Global Journal of Science Frontier Research, 2016)
Ife and Modakeke communities in South-western Nigeria have engaged in several years of communal conflicts. The conflicts have reconfigured both the economic systems and land use structure of the Central Business District of Ile-Ife. This study assessed the impact of the Ife/Modakeke crisis with emphasis on mapping the spatial realignment of land-use in the CBD and the rate of urbanization before and after the last conflict. Primary data were collected through field survey and oral interviews. The secondary data used included the base map and Land sat images of 1999 and 2015 for Ile-Ife. The period of 1999 and 2015 represents the period before and after the last conflict in 2000. GPS coordinates of some of the features were taken and plotted on the base-map extracted from the Google-Map, geo-referenced and classified into the existing land-use and land-cover types. The results showed that physical reconstructions, urbanization and new economic activities have been generally fast in Ife but relatively slow in Modakeke. The study also showed that 31% of the vegetated land-cover had been lost. The study concluded on the need for intra-communal peace for sustainable development of the two communities.